Public Relations vs Advertising - Ismail, Tengku Adrian; Ahmad, Jamilah (Penerbit UKM, 2015)
This study aims to examine and understand the effectiveness and credibility of advertising and public relations in the form of editorial coverage. This study involves three main groups, namely prominent practitioners in public relations and advertising as well as independent party who does not belong to either of these categories of practitioners. Guided by the Source Credibility Theory, this exploratory study emphasises on key measure of credibility in finding the overall effectiveness of public relations over advertising. Findings of this study provide ground for constructive argument on the co-relations, effectiveness, estrangement and togetherness of the much debated topic of public relations versus advertising. The main basis of the comparison is based on credibility, and the data focused on three central themes: contribution to brand knowledge and brand image, adequacy of public relations and advertising, and concerns of public relations and advertising practitioners. In short, both public relations and advertising can employ contextual strategy by working together to reach consumers in the most creative and tactical manner.